Hubungan Kemampuan Memahami Makna Bacaan Al-Qur'an dengan Tingkat Kecerdasan Spiritual Mahasiswa - Rizki Eka Purnairawan (Yayasan Bina Nagari Banyumas, 2025)
Understanding the meaning of Quranic recitations plays a crucial role in shaping anindividual's spiritual awareness, especially in facing the challenges of modern life.As the intellectual generation in an academic environment, students require thereinforcement of spiritual intelligence to internalize Quranic values in their daily lives.This study aims to examine the relationship between the ability to comprehend themeaning of the Quran and the level of spiritual intelligence among students at AhmadDahlan University Yogyakarta.This research employs a quantitative method with acorrelational approach to analyze the relationship between Quranic comprehensionand students' spiritual intelligence. The sample consists of 81 students from AhmadDahlan University, selected using probability sampling with a random samplingmethod. Data collection was conducted through a closed-ended questionnaireusing the Guttman scale, while data analysis techniques included Spearman's Rankand Kendall Tau correlation tests to measure the degree of association betweenthe two variables.The results indicate a significant relationship between Quraniccomprehension and students' level of spiritual intelligence. The Spearman’s Rankand Kendall Tau correlation tests yielded a significance value of 0.000 (< 0.05),with correlation coefficients of 0.552 and 0.479, respectively, indicating a moderateto weak correlation. These findings reinforce that understanding the meaningof the Quran contributes to the development of individual spiritual intelligence.Therefore, enhancing Quranic comprehension can serve as an effective strategy forstrengthening students' spiritual intelligence.